Mengkaji Perilaku Keuangan Pribadi; Fokus pada Gaya Hidup, E-Commerce, Kontrol Diri, dan Pendapatan - Sinta Devi; Sriyono; Wisnu Panggah Setiyono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research examines personal financial behavior in Sidoarjo City in the early adult generation. The aim of this research is to deepen understanding of how individuals in Sidoarjo City manage their personal finances. Quantitative methods were used with non-probability sampling techniques on 117 individuals who were working and had their own income. The results of the analysis show that there is no influence of lifestyle on financial behavior, but e-commerce and self-control have a positive and significant influence on financial behavior. Meanwhile, income has no influence on financial behavior. This research highlights the importance of financial literacy and self-control in managing personal finances, especially among the younger generation.